PENGARUH PEMBERIAN ARAS UREA PADA AMONIASI RUMPUT PALUNGPUNG (Phragmites karka) TERHADAP KANDUNGAN SERAT KASAR, PROTEIN KASAR, DAN LEMAK KASAR - Siti Choiriyah; Irene Ike Praptiwi; Dirwan Muchlis (Musamus Journal of Livestock Science, 2018)
Availability of forage in the dry season is less than the rainy season, one of the local grasses that has heat resistance, namely clumps of palungpung (Phragmites karka). This grass is hard textured so ammonia technology is carried out. This study was to determine the right concentration of urea in ammonia of palungpung grass (Phragmites karka), and to increase the nutritional value of palungpung grass (Phragmites karka) after ammoniation. The design in this study used a Completely Randomized Design (CRD). In this design there are four (4) treatments and three (3) replications. Treatment P1 = Palungpung Grass (Phragmites karka) + Urea 0%, P2 = Palungpung Grass (Phragmites karka + Urea 4%, P3 = Palungpung Grass (Phragmites karka) + Urea 8%, P4 = Palungpung Grass (Phragmites karka) + Urea 12 %. The parameters observed were crude fiber (SK), crude protein (PK), crude fat (LK). The results of variance analysis showed that the effect of urea level on ammoniation of palumpung grass (Phragmites karka) was not significantly different (P> 0.05 ) on crude fiber and crude fat content, while significantly affecting crude protein at 12% level of 17.10%.